Frequency Restoration Control and Its Impact on Model Predictive Control of Island Power Systems ... - Reus, Lucas; Alferink, Marco; Michels, Kai; Hofmann, Lutz ([Piscataway, NJ] : IEEE, 2025)
Advanced Energy Management Systems (EMSs) are proposed to achieve the economic and stable operation of low-inertia island power systems with high shares of Renewable Energy Sources (RES). However, fast power fluctuations severely affect the frequency dynamics, which are not addressed by the EMS. Thus, this paper presents the extension of a Model Predictive Control (MPC)-based EMS by a Frequency Restoration Control (FRC) that shifts the droop characteristic of a grid-forming Battery Energy Storage System (BESS) to restore the frequency. The power system of Suðuroy, Faroe Islands, consisting of RES, synchronous machines and a grid-forming BESS, serves as a case study. Quasi-stationary simulations are used to investigate both the impact of the generation units’ droop controls and the FRC on the system stability and economics. The improved frequency behavior results in less deviations of the distributed energy resources from the optimal setpoints determined by the EMS. As a result, the economic performance is ...